Brak skuteczności leczenia zespołów bólowych kręgosłupa za pomocą laseroterapii i fali ultradźwiękowej = Lack of efficacy of laser therapy and ultrasound for low back pain - Janusz Kocjan (Kazimierz Wielki University, 2016)
Kocjan Janusz. Brak skuteczności leczenia zespołów bólowych kręgosłupa za pomocą laseroterapii i fali ultradźwiękowej = Lack of efficacy of laser therapy and ultrasound for low back pain. Journal of Education, Health and Sport. 2016;6(9):323-332. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61876 http://ojs.ukw.edu.pl/index.php/johs/article/view/3805       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016.     BRAK SKUTECZNOŚCI LECZENIA ZESPOŁÓW BÓLOWYCH KRĘGOSŁUPA ZA POMOCĄ LASEROTERAPII I FALI ULTRADŹWIĘKOWEJ   LACK OF EFFICACY OF LASER THERAPY AND ULTRASOUND FOR LOW BACK PAIN   JANUSZ KOCJAN   Studium Doktoranckie Wydziału Lekarskiego w Katowicach, Śląski Uniwersytet Medyczny w Katowicach Doctoral Studium of School of Medicine, Medical University of Silesia, Katowice, Poland   Słowa kluczowe: ból kręgosłupa, dyskopatia, laseroterapia, ultradźwięki, fizykoterapia Keywords: back pain, disc herniation, laserotherapy, ultrasound, physical therapy   Streszczenie             Dolegliwości bólowe kręgosłupa stanowią jeden z najbardziej rozpowszechnionych problemów zdrowotnych na całym świecie. Skuteczne strategie leczenia tego schorzenia są jednak w dalszym ciągu ograniczone.              Celem pracy była ocena skuteczności leczenia zespołów bólowych kręgosłupa o podłożu mechanicznym za pomocą laseroterapii oraz fali ultradźwiękowej w zależności od pozycji w której wykonywano zabieg.             Materiał badawczy stanowiły 92 osoby z dolegliwościami bólowymi dolnego odcinka kręgosłupa o podłożu dyskowym. Badanych losowo przydzielono do jednej z czterech grup (każda n=23) ze względu na rodzaj przeprowadzonej interwencji zabiegowej. Wszystkich chorych oceniano dwukrotnie, przed rozpoczęciem leczenia oraz po jego zakończeniu posługując się skalą VAS (Visual Analogue Scale) oraz skalą ODI (Oswestra Disability Index).             Przed leczeniem nie stwierdzono żadnych statystycznie istotnych różnic pomiędzy grupami w zakresie analizowanych zmiennych, tj. intensywności bólu oraz poziomu niepełnosprawności. Istotną statystycznie poprawę po zastosowanym leczeniu odnotowano wśród pacjentów którym zabiegi fizykalne wykonywano w pozycji przeprostu odcinka lędźwiowego kręgosłupa oraz wśród pacjentów u których wykonywano symulowane zabiegi fizykoterapeutyczne również w pozycji przeprostu odcinka lędźwiowego. W przypadku pacjentów przebywających podczas zabiegu w zgarbionej, siedzącej pozycji (grupa interwencyjna i grupa placebo) nie odnotowano znamiennej poprawy względem danych wyjściowych.             Przeprowadzone badania i analiza uzyskanych wyników pokazują, iż fizykoterapia w postaci zabiegów laseroterapii oraz terapii falą ultradźwiękową ma znikomą wartość terapeutyczną w leczeniu zespołów bólowych kręgosłupa o podłożu mechanicznym.   Abstract             Back pain is one of the most prevalent health problems in the worldwide. However, effective strategies for treatment of this disease are still limited.             The aim of the study was to evaluate the efficacy of back pains treatment using laser and ultrasonic wave, depending on the patient position in which the therapy was performed.             Research material consisted of 92 people suffering from the pain of the lower spine caused by problems with intervertebral discs. The subjects were randomly assigned to one of four groups (each n = 23) because of the type carried out surgical intervention. All patients were evaluated twice, before treatment and after tretament using the VAS scale (Visual Analogue Scale) and ODI scale (Oswestra Disability Index).             Before treatment there were no statistically significant differences between the groups in terms of the variables considered, ie. the pain intensity and level of disability. Statistically significant improvement following treatment was observed among patients which physical procedures was performed in the position of hyperextension of the lumbar spine and among patients who performed a simulated physiotherapy also in the position of the lumbar hyperextension. In the case of patients in the hunched, sitting position (the intervention group and the placebo group) there was no significant improvement in relation to baseline.             The study and analysis of the results showed that physical therapy treatments in the form of laser and ultrasonic wave therapy is of little therapeutic value in the treatment of mechanical back pains.